Analisis Implementasi Akad Murabahah pada Pembiayaan Modal Usaha Mikro - Muhammad Abdi Syakir; Muhammad Sauqi; Mushlih Candrakusuma (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to analyze the implementation of the murabahah contract on micro business capital financing. This research is a field research by taking the location at BMT Khairul Amin Martapura. The data in this study are qualitative data consisting of primary data and secondary data. The data obtained through the method of documentation, observation and interviews. The data that has been collected is then analyzed using descriptive analysis method. The results of this study resulted in the findings that the implementation of micro business financing products using murabahah contracts at BMT Khairul Amin consisted of submitting financing by customers, fulfilling data and documents, business surveys and guarantees, administrative analysis, financing analysis, granting of wakalah authorization and financing disbursement, reporting. proof of purchase and contract of murabahah financing agreement. In practice at BMT Khairul Amin, micro business financing products that use murabahah contracts more often use wakalah contracts as complementary contracts.